Research on the Rheological Properties of the Plant Oil Pitch - Weishuai Ji; Dongpo He; Di Wu; Maryam Kargar Razi (International Journal of Chemical Engineering)
In the analysis of the rheological properties of the plant oil pitch, the original analysis method has a narrow range of analysis indicators, which affects the reliability of the analysis results. In this study, a new analytical method for the rheological properties of the plant oil pitch was designed. The microstructure characteristics of the plant oil pitch were obtained using a high-power microscope, the viscosity of the plant oil pitch was measured, and the ductility of the plant oil pitch was analyzed by setting the analysis index. The above parts are integrated, and the dynamic shear tester is used to complete the analysis of pitch rheological properties. So far, the analysis method for the rheological properties of the plant oil pitch has been designed. It can be seen from the comparison of the experimental links that this analysis method is better than the original analysis method in terms of the scope of analysis indicators. In conclusion, the analytical method of the rheological properties of the plant oil pitch is more reliable.